2014
DOI: 10.1016/j.celrep.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Expressed B7-H1 Critically Controls Intestinal Inflammation

Abstract: SUMMARY B7-H1 (PD-L1) on immune cells plays an important role in T cell coinhibition by binding its receptor PD-1. Here we show that both human and mouse intestinal epithelium expressed B7-H1 and that B7-H1-deficient mice were highly susceptible to dextran sodium sulfate- or trinitrobenzenesulfonic acid-induced gut injury. B7-H1 deficiency during intestinal inflammation led to high mortality and morbidity, which were associated with severe pathological manifestations in the colon, including loss of epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 31 publications
6
61
2
1
Order By: Relevance
“…This association supports the notion that up-regulation of PD-L1 in the gut has a potential role in human septic condition. In keeping with several other studies, increased PD-L1 expression is associated with intestinal dysfunction in patients with IBD (13,15,18).…”
Section: Junction Integritysupporting
confidence: 70%
See 2 more Smart Citations
“…This association supports the notion that up-regulation of PD-L1 in the gut has a potential role in human septic condition. In keeping with several other studies, increased PD-L1 expression is associated with intestinal dysfunction in patients with IBD (13,15,18).…”
Section: Junction Integritysupporting
confidence: 70%
“…2A). Studies showed that PD-L1 was detectable in human gastric epithelial cells (17) and colonic epithelial cells (13,15,18). We confirmed that PD-L1 mRNA and protein were constitutively expressed in freshly isolated small intestinal epithelial cells (IECs) from naïve WT mice ( Supplementary Fig.1).…”
Section: Sepsis Increases Pd-l1 Expression In the Mouse Intestinesupporting
confidence: 63%
See 1 more Smart Citation
“…PD-L1 is immuno-inhibitory and is normally up-regulated during inflammation to help minimise tissue damage 29 . Failure to express PD-L1 in the intestine enhances the risk of inflammation 32,33 but especially so when non-self antigen is being expressed 34 . Thus, not only might the nanomineral pathway ensure that luminal antigen and peptidoglycan reach sub-epithelial immune cells without enzymatic degradation en route but, additionally, it could ensure that the very cells in receipt of exogenous non-self antigens are also the ones expressing PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is expressed by B and T cells, monocytes, macrophages and dendritic cells (APCs) [8] and play important role in regulating immune responses [912]. Moreover, over-expression of PD-L1 in a variety of tumors and in-vitro experimental models indicate compromise of immune surveillance mechanism for cancer cells in the tumor microenvironment, by interaction with PD-1 [13].…”
Section: Introductionmentioning
confidence: 99%